Employees’ Perceptions of Work Attire in the Workplace, Does It Matter? - Daniel Yudistya Wardhana; Harsono Harsono (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2020)
Wearing working dress in the workplace is considered as a representation of the organization culture, work attire becomes an important factor for the employees in a workplace. The types of work attire depend on the policy and the type of the organization even though there is no certain regulation on uniform in the workplace. This study is conducted to identify the impact of employees’ attire (formal and casual) on the employees’ self-perceptions of creativity, productivity, friendliness, trustworthiness and authoritativeness and competence. This study was held in Yogyakarta. The respondents varied from the employer to the employees, with total of 147 respondents. This study found that the characteristics and the appearance of the uniform significantly affect employees’ attitude towards the job while attribute function did not seem toaffect employees’ attitude towards job.